DAMPAK MEDIA SOSIAL TERHADAP PEMBENTUKAN IDENTITAS SOSIAL ANAK DI ERA DIGITAL: SEBUAH TINJAUAN SOSIOLOGIS DI KOTA MAKASSAR - Andi Nurlela; Atma Ras; Musrayani Usman (Jurnal Neo Societal, 2024)
This study aims to analyze the impact of social media on the formation of children's social identity in the city of Makassar in the digital age. Using a qualitative approach and case study method, this research involves children aged 10-15 years who are actively using social media platforms such as Instagram, TikTok, and Facebook. The results show that social media plays a crucial role in the process of social identity formation through symbolic interaction, where children construct an ideal self-image to gain recognition and validation from their peers. However, alongside these benefits, children also face social pressures to always appear "perfect," which can affect their mental health, leading to anxiety and low self-esteem. The study further reveals that children in Makassar often experience conflicts between local cultural values, which emphasize family and cooperation, and the more individualistic global norms presented through social media. They must navigate between their real-world identities and the identities they are expected to display in the digital world. This research provides insights for parents, educators, and policymakers about the importance of healthy media literacy education and monitoring children’s social media use to help them build more positive and authentic social identities.